Pendekatan Antropologis terhadap Tradisi Keislaman Lokal - Asmar Habibi; Julhadi Julhadi; Sri Wahyuni (Lembaga Yasin AlSys, 2026)
Studies on Muslim religious practices have been widely conducted; however, research that specifically examines local Islamic traditions through an anthropological lens remains limited, as most previous studies have focused on the normative dimensions of religious doctrine and have not extensively explored the symbolic meanings and socio-cultural functions of local religious traditions. This study aims to describe the forms of local Islamic traditions, analyze the religious meanings embedded within them, and explain their socio-cultural functions in community life. A qualitative approach with an ethnographic design was employed, involving religious leaders, customary leaders, and community members selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using thematic analysis through the stages of coding, categorization, and conclusion drawing. The findings show that local Islamic traditions continue to be actively practiced in various forms of ritual and social–religious activities, which are understood as media for strengthening religious values, preserving cultural identity, and fostering social solidarity. The continuity of these traditions is shaped by religious understanding, cultural commitment, and the dynamics of modernization faced by the community. These results contribute to the anthropology of religion by clarifying the relationship between Islam and local culture and affirm that local Islamic traditions play a strategic role in maintaining social harmony and communal religiosity. The implications of this study include theoretical contributions to the development of Islam Nusantara scholarship and practical implications for stakeholders in formulating strategies to preserve traditions grounded in local wisdom.